Smart Transportation Systems 2019 - Qu, Xiaobo; Zhen, Lu.; Howlett, Robert J.; Jain, Lakhmi C.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
The book gathers selected papers presented at the KES International Symposium on Smart Transportation Systems (KES-STS 2019). Modern transportation systems have undergone a rapid transformation in recent years. This has produced a range of vehicle technology innovations such as connected vehicles, self-driving cars, electric vehicles, Hyperloop, and even flying cars, and with them, fundamental changes in transport systems around the world. The book discusses current challenges, innovations and breakthroughs in Smart Transportation Systems, as well as transport infrastructure modeling, safety analysis, freeway operations, intersection analysis, and other related cutting-edge topics.
An Algorithm for Reducing Vehicles' Stop Behind the Bus Pre-Signals -- Estimation Models for the Safety Level of Indoor Space Pedestrian Flows -- Station-Level Hourly Bike Demand Prediction for Dynamic Repositioning in Bike Sharing Systems -- Study of Data-Driven Methods for Vessel Anomaly Detection Based on AIS Data -- Estimation Method of Saturation Flow Rate for Shared Left-Turn Lane at Signalized Intersection, PartⅠ:Methodology -- Estimation Method of Saturation Flow Rate for Shared Left-Turn Lane at Signalized Intersection, PartⅡ: Case Study -- Safety on Italian Highways, Impacts of the Highway Chauffeur System -- Restorable Robustness Considering Carbon Tax in Weekly Berth and Quay Crane Planning.
Keywords: Engineering -- Data processing; Transportation engineering; Traffic engineering; Big data; Data Engineering; Transportation Technology and Traffic Engineering; Big Data